Holistic Localized Performance Assessment for Agroecology (HOLPA) survey - Sanchez Bogado, Andrea Cecilia; Jones, Sarah; Lamanna, Christine (2024)
The farm-household level HOLPA involves an interview, and fieldwork surveys, ideally conducted jointly with the household head. The interview survey collects data on context, adherence to agroecology principles, and agronomic, environmental, economic, and social performance. The fieldwork survey provides an on-site assessment of respondent and farming system context, while gathering observational data related to four key performance themes: biodiversity, climate mitigation, crop and pasture health, and soil health.